The Influence Of Digital Financial Literacy And Locus Of Control On Financial Satisfaction Mediated By Financial Well-Being Among Generation Z In Jambi City - Ervina Oktavia Rizki; Besse Wediawati; Andang Fazri (International Journal of Economics, Business and Innovation Research, 2025)
This study aims to determine the effect of digital financial literacy and locus of control on financial satisfaction, mediated by financial well-being among Generation Z in Jambi City. The study adopts a quantitative approach using the Cochran formula for sampling. The sample in this study amounted to 96 respondents. Data were collected through questionnaires measured on a Likert scale. The data analysis method used was Partial Least Square (PLS), processed using SmartPLS 3.0 software. The results indicate that both digital financial literacy and locus of control have a significant effect on financial satisfaction. Digital financial literacy also has a significant positive effect on financial well-being. However, locus of control does not significantly affect financial well-being. Furthermore, financial well-being mediates the relationship between digital financial literacy and financial satisfaction, but it does not mediate the relationship between locus of control and financial satisfaction.